Using Cooling to Enhance Heat Acclimation and Endurance Performance - Ramos, Julian (Curtin University, 2024)
This thesis explored using cooling to enhance heat acclimation and exercise performance. I present evidence that cooling provides the largest benefit to endurance performance in hot-humid conditions. When both heat acclimation and cooling are combined in a single session, exercise intensity is improved, without compromising the stimulus and physiological responses to heat. However, when applied over a full protocol, no adaptation was observed, but exercise performance was maintained compared to heat acclimation training alone.